Deixis In Sandiaga Unos Expression In Talk Show Tv Program - Putri Septi Ayu Ningsih (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2023)
This study with the types of deixis in Sandiaga Uno?s expression in talk show tv program. The objectives of this study are to find out the types of deixis that are used by Sandiaga Uno?s, to investigate the deixis used in the talk show and to reason for the use of deixis by Sandiaga Uno?s expression. The data this study was the one selected video taken as the sample. The findings of this study showed that those five types of deixis were found in Sandiaga Uno?s expression, they are: person 150 (63.55%), spatial 12 (5.08%), temporal 17 (7.20%), discourse 38 (16.10%), and social 19 (8.05%). The most dominant types of deixis found in Sandiaga Uno?s Expression were person deixis and the deictic word I and We were the dominant deictic words that Sandiaga Uno?s used in expression which interpreted that Mr. Sandiaga Uno is a firm and unobtrusive vice president.